Yield Comparison of Sticky Rice 7 Varieties at Sikai Village Xayboury District Savannakhet Province - PIYADETH, Santi (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
yield Comparison of Sticky Rice 7 Varieties at Sikai Village Xayboury District Savannakhet Province, the objective of research 1). Yield components comparison of sticky rice 7 varieties and 2) Yield comparison of sticky rice 7 varieties, the experiments were arranged in Randomized Complete Block Design with 4 replications and 7 treaments such as: Xaybangphai 2, Xaybangphai 3, Thadokkham 8, thadokkham 11, thasano8, thasano 9 and Sanpathong. For data analysis were: Anlysis of variance and mean coparison by DMRT model. The result wererevealed: weight of 1,000 seeds, weight of spikelet, length of spikelet, number of stem per clump and number of withered seed were significantly (P-value≤0.01): thadokkham11 gave hiegestin weight of 1,000 seeds (131.34g) and weight of spikelet (9.43g), thadokkham11 and thassano 9 gave lowest in withered seed (8.30 and 8.05 seed), thadokkham11 and sanpathong gave heighest in length of spikelet (24.40 and 24.10 cm) and number of stem per clump (18.74 and 18.82). For height of harvesting, seed per spikelet and best seed per spikelet were significant (P-value≤0.05): thadokkham 8, thadokkam11 and thasano8 gave heighestin best seed (73.53, 74.73 and 73.35 seed), thadokkham11, thasano8 and sanpathong gave heighest in seed per spikelet (83.33, 85.18 and 83.50 seed), thadokkham8 and thasano8 gave heighest in heigh of harvesting (120.45 and 124.92 cm). For Yield comparison were significantly (P-value≤0.01): thadokkham11 and sanpathong gave heighest yield 3,969and 3,920 kg per hectar.